2002
DOI: 10.1524/zpch.2002.216.5.555
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Excitation Spectrum, Lifetimes and Photoisomerization of Jet-Cooled Conformers of 1,1´-bi(benzocyclobutylidene)

Abstract: Fluorescence Excitation Spectra / 1,1 -bi(benzocyclobutylidene) / PhotoisomerizationFirst measurements of fluorescence excitation spectra of the recently synthesized rigid stilbene analogue 1,1 -bi(benzocyclobutylidene) in a supersonic jet expansion show that, in contrast to the parent compound, both the trans-and the cis-conformer fluoresce under these conditions. The excitation energy dependence of fluorescence lifetimes indicates the onset of an efficient non-radiative decay channel above energy thresholds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…Recently, we presented a similar comparison between measurements of k(E) and the corresponding calculated k ∞ with measured thermal rate coefficients k nr in low viscosity solutions for the trans- and cis -conformers of benzocyclobutenyliden-benzocyclobutene . While, for the cis -isomer, the two rate constants agreed to within better than 10% (1.2 and 1.3 × 10 10 s -1 , respectively), for the trans -isomer there was a factor of 2−3 discrepancy (1.8 versus 4.6 × 10 9 s -1 ) which may be considered as still close to the experimental uncertainty.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Recently, we presented a similar comparison between measurements of k(E) and the corresponding calculated k ∞ with measured thermal rate coefficients k nr in low viscosity solutions for the trans- and cis -conformers of benzocyclobutenyliden-benzocyclobutene . While, for the cis -isomer, the two rate constants agreed to within better than 10% (1.2 and 1.3 × 10 10 s -1 , respectively), for the trans -isomer there was a factor of 2−3 discrepancy (1.8 versus 4.6 × 10 9 s -1 ) which may be considered as still close to the experimental uncertainty.…”
Section: Resultssupporting
confidence: 60%
“…The ambiguity of the situation has led us to a new attempt to solve the dilemma. Improved possibilities to calculate vibrational frequencies for excited electronic states by ab initio methods allowed us to do such calculations for a series of diphenylpolyenes. The surprising accuracy of the calculated frequencies for those vibrations, where a comparison could be made, provides confidence that the calculations are essentially correct.…”
Section: Introductionmentioning
confidence: 99%
“…The X-ray structure of trans - 1 showed that the molecule is planar . Photophysical and photochemical properties of the trans isomer along with a series of other cyclic stilbenes were investivated. , …”
Section: Introductionmentioning
confidence: 99%
“…In 2002, Lenoir and associates reported on the synthesis of sterically hindered stilbene 1,1′-bi(benzocyclobutenylidene) 1 (Figure ) by McMurry coupling of benzocyclobuten-1-one, resulting in a 1:1 mixture of cis and trans isomers, along with the isomeric diols 2 , which were obtained as minor products. The pure trans isomer of 1 was isolated on small scale by semipreparative HPLC or by crystallization techniques . The X-ray structure of trans - 1 showed that the molecule is planar .…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, other photochemical activation systems could be interpreted satisfactorily under the assumption that the thermal energy of the ground state in absorption together with the photon energy was carried up more or less undistorted into the excited electronic state. Examples of such systems are alkyl-substituted cycloheptatrienes and benzenes, 1,1‘-(benzocyclobutylidene), and also NO 2 . Why should trans -stilbene photoisomerization be governed by Franck−Condon cooling while all of these other systems do not show evidence for such effects?…”
mentioning
confidence: 99%